A non‐vector herbivore indirectly increases the transmission of a vector‐borne virus by reducing plant chemical defences. (13th February 2020) - Su, Qi; Yang, Fengbo; Yao, Qixi; Peng, Zhengke; Tong, Hong; Wang, Shaoli; Xie, Wen; Wu, Qingjun; Zhang, Youjun
Abstract: Vectors and viruses exist in communities consisting of many interacting species. Although the cascading effects of predators or parasitoids on disease spread via direct effects on vectors have been investigated, little is known about the effects of other free‐living species in communities on the transmission of vector‐borne viruses via indirect (host‐plant mediated) effects on vectors. In the present study, we used a food web consisting of tomato plants Solanum lycopersicum, two tomato herbivores (the vector whitefly, Bemisia tabaci, and the non‐vector two‐spotted spider mite, Tetranychus urticae ) and a whitefly‐vectored plant virus ( Tomato yellow leaf curl virus, TYLCV) to study how T. urticae may affect TYLCV transmission by B. tabaci via host‐plant mediated effects on B. tabaci . We found that T. urticae infestation promoted B. tabaci feeding, thereby increasing TYLCV transmission to tomato plants. These increases were associated with T. urticae ‐induced reductions in two flavonoids (rutin and quercetin trisaccharide) of tomato plants. Elevation of rutin and quercetin trisaccharide levels in T. urticae ‐infested plants via exogenous stem applications reduced B. tabaci feeding and TYLCV transmission. Therefore, suppression of these flavonoids by T. urticae infestation was the most likely explanation for the observed changes in B. tabaci feeding behaviour and TYLCV transmission. Our results show that by reducing flavonoids in tomato plants, a non‐vector herbivore can indirectly increase the transmission of a vector‐borne plant virus. These findings indicate that species that are far removed from the direct vector–virus interactions can indirectly affect vector‐borne virus transmission by altering the chemical defences of the shared host plant. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.